Jerapan sianida pada permukaan tanah baki granit dan lempung - Mohd Raihan Taha; Debnath Depankar; Shamala Peramayah (1999)
Soil pollution is a widespread problem in developing countries due to uncontrolled disposal of waste. Thus a study related to soil-pollutant interaction is necessary to study contaminant behaviour and its migration to surrounding areas. It will also help to plan necessary mitigation and clean-up measures for contaminated land. One study which will provide significant input to this cause is the soil- contaminant adsorption kinetics, as conducted in this research program Two types of soil were used, i.e. granite residual soil and kaolinite. The adsorption interaction between these two on cyanide were then compared. Data obtained showed that the granite. residual soil adsorbed more cyanide than that of kaolinite. The Kd value of 0.64 and 0.022 for granite residual soils and kaolinite, respectively, obtained from laboratory tests proved this point. Moreover, other adsorption parameters showed significant differences between the two soils. This is possibly because the granite residual soil have a higher organic content and clay fraction than kaolinite. Also the residual soil is less negatively charged than kaolinite as shown by its more acidic pH. The results also reveal that residual soils may be an option to kaolinite for use as landfill liners